2022
DOI: 10.1007/s00270-022-03187-y
|View full text |Cite
|
Sign up to set email alerts
|

Holmium-166 Radioembolization: Current Status and Future Prospective

Abstract: Since its first suggestion as possible option for liver radioembolization treatment, the therapeutic isotope holmium-166 (166Ho) caught the experts’ attention due to its imaging possibilities. Being not only a beta, but also a gamma emitter and a lanthanide, 166Ho can be imaged using single-photon emission computed tomography and magnetic resonance imaging, respectively. Another advantage of 166Ho is the possibility to perform the scout and treatment procedure with the same particle. This prospect paves the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 32 publications
0
29
0
3
Order By: Relevance
“…TARE is usually performed with Yttrium-90 (90Y) in resin or glass microspheres (although there are ever-increasing reports regarding the effectiveness of Holmium-166 (166Ho) in poly(L-lactic acid) (PLLA) microspheres) [ 95 ]. As opposed to TACE, TARE utilizes local beta radiation to achieve tumor necrosis instead of artery occlusion.…”
Section: Endovascular Treatments and Immuno-oncologymentioning
confidence: 99%
“…TARE is usually performed with Yttrium-90 (90Y) in resin or glass microspheres (although there are ever-increasing reports regarding the effectiveness of Holmium-166 (166Ho) in poly(L-lactic acid) (PLLA) microspheres) [ 95 ]. As opposed to TACE, TARE utilizes local beta radiation to achieve tumor necrosis instead of artery occlusion.…”
Section: Endovascular Treatments and Immuno-oncologymentioning
confidence: 99%
“…These Monte Carlo simulations are for now only used in research and development, involving important computer processing resources and time, with software that is not commercialized nor available for routine clinical use. Therefore, the monocompartmental model is recommended using 166 Ho microspheres, targeting a maximum of 60 Gy to the whole liver volume [ 70 ]. Nevertheless, a recent study evaluating post-therapy 166 Ho SPECT/CT dosimetry demonstrated a dose response relationship and a better outcome for patients treated with a tumor absorbed dose of at least 90 Gy (for colorectal metastases).…”
Section: Pre-therapy Imaging With 166 Ho Spect/ctmentioning
confidence: 99%
“…Therefore, some theranostic radiopharmaceuticals have been explored in the past to substitute 90 Y-microspheres in liver radioembolization. For example, Holmium-166 ( 166 Ho)-poly-L-lactic acid (PLLA) microsphere has received Conformité Européenne (CE) certification in 2015 under the commercial name QuiremSpheres™ (Quirem BV, Deventer, the Netherlands) [ 7 ]. There are some other potential theranostic radionuclides such as Iodine-131 ( 131 I) and Rhenium-188 ( 188 Re) [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%